Hi there! Have questions about your homework? At Brainly, there are 60 million students who want to help each other learn. Questions are usually answered in less than 10 minutes. Try it for yourself by posting a question! :D

Hi there! Have questions about your homework? At Brainly, there are 60 million students who want to help each other learn. Questions are usually answered in less than 10 minutes. Try it for yourself by posting a question! :D

Since the formula of sun of nth term in A.P is n/2{2a+(n-1)d}nowS1=n/2{2a+(n-1)d}S2=2n/2{2a+(2n-1)d}S3=3n/2{2a+(3n-1)d}S2-S1=n/2{2a+(3n-1)d} therefore3(S2-S1)=3n/2{2a+(3n-1)d}=S3 hpe i helped u plz mark as brainiest answer plz